ANALISIS YURIDIS HASIL ANALITIK ARTIFICIAL INTELLIGENCE SEBAGAI BUKTI PENYIDIKAN MENURUT UU 20 TAHUN 2025 - Priantama Putra; Hendri Jayadi; Tatok Sudjiarto (Honeste Vivere, 2026)
The rapid integration of Artificial Intelligence (AI) technologies, notably facial recognition and digital forensics, has profoundly reshaped criminal investigations within the justice system. The enactment of Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code (KUHAP) formally recognizes electronic evidence, consequently prompting critical inquiries regarding the legal status and probative value of AI-generated analytics. This research investigates the juridical standing of AI-derived analytics in Indonesia’s evidentiary framework and evaluates the legal hurdles surrounding their implementation. By utilizing a normative legal methodology with statutory, conceptual, and comparative approaches, the collected data undergoes a deductive qualitative analysis. Findings indicate that AI analytics fail to qualify as independent evidence under the KUHAP. Instead, they strictly function as corroborative proof, categorized as electronic evidence, expert testimony, or circumstantial indicators (petunjuk). Their admissibility inherently depends on legal data acquisition, algorithmic accuracy, data integrity, expert verification, corroboration with legitimate evidence, and judicial conviction. Furthermore, multifaceted challenges persist, encompassing systemic opacity, algorithmic bias, data privacy vulnerabilities, human rights concerns, and a void in AI-specific regulations. Ultimately, Indonesia urgently requires a comprehensive legislative framework governing AI to guarantee legal certainty, accountability, transparency, human oversight, and the safeguarding of fundamental rights during equitable and fair criminal investigations.